Internationalization strategies and methods of construction firms – a comparative study between Hong Kong - Chinese and Portuguese – European approaches - Gabriel, Delfino Azinheira (2014)
Dissertação para obtenção do Grau Mestre em Engenharia Civil – Perfil de Construção